The Efficiency of an Instructional Program based on Discrimination Teaching Strategies On the Achievement of Students in the Tenth Grade of Literature in Geography - محمد عارف کارزان; عبدالرحمن جمعة علي; حمید محمد شاد (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
The aim of the research is to prepare an educational program based on (3) different strategies of educational strategies differentiated and the effectiveness of that program each of those strategies on the achievement of tenth grade students in Geography and The research followed the descriptive approach to preparing the program and the semi-experimental approach to applying the program in order to reach the research objectives through a zero hypothesis, which is: There are no statistically significant differences at the level (0.05) between the average scores of students in the experimental groups who study by teaching lessons based on the proposed program with differentiated education strategies (Think-Pair-Share, jigsaw, graded activities), and the average scores of students in the control group, in a test achievement. The research community consisted of preparatory school students in the city of Sulaymaniyah, who chose a sample for his research intentionally in the school (preparatory school of Dr. Ezzedine Mustafa Rasool). It included (100) students and divided equally into four sections, as each group includes (25) students. After they were rewarded according to the variables (chronological age, previous knowledge, intelligence and achievement to be ahead of the subject in sociology), then they were divided randomly into (3) experimental groups, where each group was taught according to an educational strategy from the strategies of differentiated education, and a control group that was taught in the usual way. (100) students divided equally into four classes, each class comprising (25) students. After they were rewarded according to the variables (chronological age, prior knowledge, intelligence and achievement to be ahead of the subject in sociology), then they were randomly divided into (3) experimental groups, where each group was taught according to an educational strategy from the strategies of differentiated education and a control group that was taught in the usual way. The researcher prepared an exam to obtain the achievement of students consisting of 30 paragraphs and in the form of choices and then found the sincerity of the internal and according to the table of specifications and the sincerity of virtual by experts and the researcher got stability through repetition of the test on another group of students at the same stage consisting of (50) students and at two different times the period between the two times took two weeks and the value of stability ((0.84). The research data was processed using the following statistical methods: (One Way Anova), Pearson’s correlation coefficient, and Eta-square, the Fisher equation, the Cooper equation and the researcher concluded that there were statistically significant differences between each of the first, second, and third experimental groups compared to the control group, and the differences were Between the three strategies in the interest of the second strategy (Jigsaw).